El impacto de las revistas juveniles generación 21 y la onda en los alumnos de entre 13- 17 años del colegio miraflores - Salazar Cubillo, Paola Andrea (2016)
The present thesis project under the title THE IMPACT OF THE JUVENILE MAGAZINES GENERATION 21 AND THE WAVE IN THE PUPILS OF BETWEEN 13 - 17 YEARS OF THE SCHOOL “MIRAFLORES“, has the intention of reflecting in how two of the most popular juvenile magazines in our country, have an influence in cognitive aspects of the young people in the development of personality, conduct and the formation that they deliver. In this text we announce, with exclusive professionals interviews in the sociology, psychology and communication, the form in which the young people is attracted by these publications with dyes of juvenile stereotypes, layout coloring and infested with images that so much demonstrates to be a taste of the adolescents. The used population there were the students of the School Miraflores, with an age status between the 13 to 17 years. The same ones that helped us to give him answers to our hypotheses and in turn they supported us with opinions with regard to the topic to contribute major information to the present work…………